2021
DOI: 10.1039/d0bm01306d
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a hierarchical micro & nanoporous surface for loading genistein on the composite of polyetheretherketone/tantalum pentoxide possessing antibacterial activity and accelerated osteointegration

Abstract: Nanoporous tantalum pentoxide (NTP) particles with pore size of around 10 nm were synthesized and blended with polyetheretherketone (PEEK) to fabricate PEEK/NTP composite (PN). Subsequently, PN was treated by concentrated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Antibiosis and anti‐inflammation can eliminate cough‐related incentives, and dilation of blood vessels can help dilute irritants in the blood, thereby reducing the cough (Xue‐jian et al, 2011). Among the core antitussive components obtained, quercetin, genistein, luteolin, kaempferol and emodin have explicit antibacterial, anti‐inflammatory and vasodilatory effects (Dong et al, 2016; Jaiswal et al, 2019; Li et al, 2016; Mei et al, 2021; Ren et al, 2019; Wu et al, 2020). Quercetin can relieve acute lung injury induced by cigarettes, and has a significant antitussive effect when combined with mangiferin (da Silva Araújo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Antibiosis and anti‐inflammation can eliminate cough‐related incentives, and dilation of blood vessels can help dilute irritants in the blood, thereby reducing the cough (Xue‐jian et al, 2011). Among the core antitussive components obtained, quercetin, genistein, luteolin, kaempferol and emodin have explicit antibacterial, anti‐inflammatory and vasodilatory effects (Dong et al, 2016; Jaiswal et al, 2019; Li et al, 2016; Mei et al, 2021; Ren et al, 2019; Wu et al, 2020). Quercetin can relieve acute lung injury induced by cigarettes, and has a significant antitussive effect when combined with mangiferin (da Silva Araújo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Mei et al loaded GT on the 3D network structure of tantalum pentoxide and PEEK composites, obtained by concentrated sulfuric acid sulfonation. The antibacterial rates of the GT loaded materials were 88.2% against S. aureus and 100% against E. coli , indicating that GT‐loaded material had a significant antibacterial effect on S. aureus and E. coli 26 …”
Section: Antibacterial Coatingmentioning
confidence: 99%
“…The antibacterial rates of the GT loaded materials were 88.2% against S. aureus and 100% against E. coli, indicating that GT-loaded material had a significant antibacterial effect on S. aureus and E. coli. 26…”
Section: Genisteinmentioning
confidence: 99%
“…Cell experiments demonstrated that when compared with PN, the adhesion, proliferation, and osteogenic differentiation of rBMSCs on SPN and SPNG were enhanced. In animal experiments, SPN and SPNG had greater bone formation than PN [ 205 ].…”
Section: Anti-infective Functionmentioning
confidence: 99%
“… [ 203 ] Concentrated sulfuric acid, Ta, GS In vitro : TPSG exhibits excellent antibacterial properties; increased cytocompatibility and differentiation of MG-63 ​cell; In vivo : enhanced bone regeneration and osseointegration [ 86 ] NTP, concentrated sulfuric acid, GS In vitro : Cytocompatibility and differentiation increased gradually in PN, SPN, and SPNG; showed excellent antibacterial activity on SPNG; In vivo : bone formation was successively enhanced in PN, SPN, and SPNG. [ 205 ] Coating antibiotics CaHPO 4 ·2H 2 O, GS In vitro : increased cytocompatibility and differentiation; had incredible antibacterial properties; In vivo : exhibited excellent antibacterial activity and osteointegration in femoral defect infection of rat experiments. [ 211 ] GS, SF, AgNPs In vitro : increased cytocompatibility and differentiation; had remarkable antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%